King Salmans visit reaffirms strong ties via trade deals - News Straits, Times (New Strait Times, 2017)
KUALA LUHPUR: The recent visit by Saudi Arabia's King Salman Abdulaziz A1 Saud to Malaysia brought forth bilateral relations pitch that is described as "an alltime high" between the two countries.